The Influence of Work Motivation and Work Environment on the Performance of Employees at the Barru Regent's Office in 2020-2024 - Andi Marwati; Syahrir; Adrianah (LP2M IAIN Palopo, 2025)
The purpose of this study was to determine the Influence of Work Motivation and Work Environment on the Performance of Employees at the Barru Regency Regent's Office The analysis method used in this study is multiple linear regression analysis, T test, F test, correlation analysis and determination. The results of the study indicate that the hypothesis of work motivation on Employee Performance is accepted on the basis of a calculated T value of 6.329 which is greater than the T table value of 1.6643, in addition, the hypothesis of the work environment on Employee Performance is accepted on the basis of a calculated T value of 4.687 which is greater than the T table value of 1.6643. the results of the calculation on the F test show that Work Motivation and Work Environment have a simultaneous effect on Employee Performance on the basis of a calculated F value of 67.280 which is greater than the F table 3.11. then the results of the correlation coefficient test show that Work Motivation and Work Environment have a strong relationship with employee performance, then based on the results of the determination test, it shows that the contribution of Work Motivation and Work Environment is 62.1% to the Employee Performance variable.